2017
DOI: 10.1007/s00216-017-0578-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood adsorption onto dialysis membranes by time-of-flight secondary ion mass spectrometry and near-field infrared microscopy

Abstract: Blood adsorption onto the inside surface of hollow fiber dialysis membranes was investigated by means of time-of-flight secondary ion mass spectrometry (TOF-SIMS) and near-field infrared microscopy (NFIR) in order to evaluate the biocompatibility and permeability of dialysis membranes. TOF-SIMS is useful for the imaging of particular molecules with a high spatial resolution of approximately 100 nm. In contrast, infrared spectra provide quantitative information and NFIR enables analysis with a high spatial reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The different pore size distribution between the two materials (homogeneous for CTA, smaller‐sized pores on the inside surface than on the outer surface for ATA) could also play a role . The low tendency of ATA polymer to adsorb proteins has also been shown in a recent study by means of TOF‐SIMS and near‐field infrared microscopy …”
Section: Discussionmentioning
confidence: 82%
“…The different pore size distribution between the two materials (homogeneous for CTA, smaller‐sized pores on the inside surface than on the outer surface for ATA) could also play a role . The low tendency of ATA polymer to adsorb proteins has also been shown in a recent study by means of TOF‐SIMS and near‐field infrared microscopy …”
Section: Discussionmentioning
confidence: 82%
“…Thus, differences in the adsorbed mass due to convection were barely detected. Moreover, the specific adsorption potential of PA, PS and CTA membranes in HD were focused on essential proteins and immunoglobulins as obtained by several studies [32][33][34][35] . Our results are in total agreement with the data presented, among others, by Urbani et al 36 , as we found that β 2 -microglobulin was detected in greater quantities in PS membranes than in CTA membranes, whereas albumin was more present in CTA than in PS in the non-convective modality.…”
Section: Discussionmentioning
confidence: 99%
“…Modern polymer technologies allow fabrication of synthetic membranes with predetermined geometry of pores (see, for the review, [151,152,153,154,155,156,157,158,159,160,161]). Silicon membranes are convenient objects for the analysis of the effects of pore size and pore geometry.…”
Section: Fundamental Thermodynamic Relations For the Transport Of mentioning
confidence: 99%
“…Since HD blood purification demands multidisciplinary efforts, both improvements in engineering and continued search for the optimal filters in biomedicine need to proceed along with clinical studies of new synthetic materials. The main goal of the improved filtration in hemodialysis (HD) is to designing artificial polymer membranes for dialysis capillary filters that have special properties [155,156,157,158,159,160]. This general perspective involves several aspects.…”
Section: Water Transport Across Artificial Dialysis Membranesmentioning
confidence: 99%
See 1 more Smart Citation